Analisis Faktor Penyebab Perbedaan Biaya Riil dengan Tarif INA-CBG’s pada Pasien Operasi Odontektomi di RSUD Jagakarsa Tahun 2023 - Prima, Dero; Kosasih; Noor, Laili Savitri (PendIPA Journal of Science Education, 2026)
Impacted of the teeth is a common condition for 0.8-3.6% of population, can become a ealth care issue that affect quality of life and productivity that low the economics level. Odontectomy is one of the methods that can fix impacted teeth. This research is to look for the cause and factors that make the difference between real cost from INA-CBGs rates. This research is a descriptive observational, the data taken retrospective and cross sectional. The samples are odontectomy patient that admitted to Jagakarsa Hospital in January – December of 2023. The analysis used Mann Whitney test and multivariate correlation analysis to determine the relation between real cost and INA-CBG’s rates. 285 samples showed that there are statistically different from hospital real cost, which shown higher, and INA-CBGs rate in odontectomy patient (p<0.001). Analytic multivariate correlation shown that pharmacy (p<0.001), length of stayed (p<0.001), and odontectomy procedure (p<0.001) are significant factor that cause higher hospital real cost. The highest factor that influenced hospital real cost is pharmacy (r=0.728), followed by length of stay (0.487) and odontectomy procedure (r=0.348).